Pemanfaatan ICT Dalam Pembelajaran PAI - Sahmiar Pulungan (Query: Journal of Information Systems, 2017)
The purpose of this research is to know how teaching learning Islamic education by using computer and to know students’ motivation in learning Islamic education by using komputer. The Islamic education teaching material  has been used in teaching-learning and it can be used Microsoft Office Powerpoint as a media presentation and digital material using SOM application. The use Microsoft Office Powerpoint in Teaching-learning Islamic education and digital material will reach the goal of teaching-learning Islamic education and it can motivate students so the teaching-learning can be more efficient.